Mathematical modelling of the container cranes under seismic loading and proving by shake table - Azeloglu, C. Oktay; Sagirli, Ahmet; Edincliler, Ayse (SPRINGER, 2013)
This paper is concerned with modelling of the behaviour of container cranes under seismic loadings. For this purpose, physical and mathematical models are prepared. A six degrees-of-freedom non-linear mathematical model is developed in order to understand the dynamic behaviour of cranes under the seismic loadings. In order to determine the seismic behaviour of the container cranes against earthquakes, a 1/20 scaled crane model was designed and constructed. For the comparison of the models, the real earthquake records were used. The results are used to observe the destructive effects and compared with the period values of the most critical sections on the crane structure. When time and frequency domains are compared, it is seen that mathematical modelling of the container crane structure shows reasonable results under dynamic loadings. It will be available to take precautions and to increase seismic performance of cranes with the help of the developed dynamic model. Also, the developed mathematical model will be able to be used as a crane model in active vibration control studies in order to decrease the structural vibrations on container cranes.
Keywords: Container cranes; Structural vibrations; Non-linear mathematical model; Shake table tests; 1/20 scaled crane model; NONLINEAR STRUCTURAL SYSTEM; FUZZY-LOGIC CONTROL; EARTHQUAKE; VIBRATION; ATMD; Engineering; Mechanics